Penggunaan Model Indeks Tunggal Untuk Investasi Portofolio Saham Di Bursa Efek - Halkadri Fitra (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2017)
This study aims to determine: 1) the value of return and risk of individual securities shares, 2) the value of return and risk stock portfolio, 3) the value of return and risk of optimal portfolios using single index model and 4) determine stocks of companies that can be community options listed in the Jakarta Islamic Index. This research was conducted using secondary data obtained from the Indonesia Stock Exchange in the form of IDX monthly and annually, ICMD and as well as data from secondary documents other with the object of research is all the shares of companies listed in the Jakarta Islamic Index Indonesia Stock Exchange from January 2013 to September 2016. The results showed that the average return is the highest individual share with a value of 0.4060 contained in the company of PT. Perusahaan Gas Negara (Persero), Tbk. and the lowest was in the company of PT. PP London Sumatra Indonesia Tbk with a value -0.3488. As for the shares that the highest variance is worth 0.0233 on PT. PP London Sumatra Indonesia Tbk, and the smallest is worth 0.0033 contained in the company of PT. Telekomunikasi Indonesia (Persero), Tbk. Furthermore, the market return is worth 0.0055, and market risk is worth 0.0017 and the return expectations of the portfolio is worth 0.01808, while the variance portfolio worth 0.00545. Research also get a result there are three that form the optimal portfolio of securities, namely PT. Telekomunikasi Indonesia (Persero), Tbk with a share of 45.95%, followed by PT. Indofood CBP Sukses Makmur, Tbk with a share of 27.76%, and the latter is PT. Unilever Indonesia, Tbk with a portion of 26.29%.